Antiracist storytelling: latinx graduate students and faculty experiences in academia. Issue 1 (2nd January 2023) - Fernandez, Mariela; Pola, Alicia; Rose, Jeff; Harris, Brandon
ABSTRACT: Anti-racist storytelling serves as a mechanism to expose the power dynamics and structural racism embedded in U.S. society. The goal of this paper is to demonstrate how anti-racist storytelling can be germane to challenging the status quo in academia that allows inequities to exist. First, we begin by sharing and debriefing stories that illustrate the difficulties that Latinxs face within academic spaces. Second, we discuss the role of allies. Finally, we present a story of faculty engaging in a dinner discussion, which highlights the issues of power, representation, and voice in who gets to share the stories of people of colour. Critical race theory (CRT) guided the development of these stories, and a short discussion on the framework is included.